Prevalence of airflow obstruction in patients attending a rapid access chest pain clinic - Francis, Helen C.; Colecliffe, Wendy; Hazell, Michelle L.; Singh, Dave; Niven, Robert; Hagan, Gerry W.; Spencer, Michael D.; Frank, Timothy L. (Respiratory medicine, 2009)
Many UK hospitals have set-up specialised chest pain clinics to deal promptly and efficiently with cases of possible cardiac chest pain. It is possible that a proportion of patients attending these clinics will have a respiratory cause for their chest pain, or respiratory disease in addition to their cardiac pain. This study aimed to determine the prevalence of airflow obstruction, ischaemic heart disease and dual pathology in such patients. Spirometry was performed on patients referred to a rapid access chest pain clinic over a 12-month period (target population of 400 patients). The main outcome measure was the prevalence of airflow obstruction (defined using spirometry), ischaemic heart disease and dual pathology. 405 subjects participated in the study. Abnormal spirometry was detected in 21% of patients ( n = 85). Airflow obstruction was the predominant lung function abnormality and was detected in 60 patients. Ischaemic heart disease was diagnosed in 21% of patients ( n = 85). Dual pathology was found in 4% of patients ( n = 17). Previous studies have reported a link between impaired lung function and future cardiovascular morbidity and mortality. This study suggests that airflow obstruction is an important alternative differential diagnosis in patients referred to a rapid access chest pain clinic. The identification of abnormal spirometry may help to better risk-stratify patients for future cardiovascular events and allow interventions to be instituted.